Retraction Note: Nanosilver-functionalized polysaccharides as a platform for wound dressing - Syam Mohan; Pranay Wal; Kamla Pathak; Madhusmruti Khandai; Tapan Behl; Hassan A. Alhazmi; Gulrana Khuwaja; Asaad Khalid (Environmental Science and Pollution Research, 2025)

Molecular Chaperones as Therapeutic Target: Hallmark of Neurodegenerative Disorders - Aditi Sharma; Om Prakash Shah; Lalit Sharma; Monica Gulati; Tapan Behl; Asaad Khalid; Syam Mohan; Asim Najmi; Khalid Zoghebi (Molecular Neurobiology, 2024)

Mitochondrial Dysfunction as a Signaling Target for Therapeutic Intervention in Major Neurodegenerative Disease - Shubhada V. Mangrulkar; Nitu L. Wankhede; Mayur B. Kale; Aman B. Upaganlawar; Brijesh G. Taksande; Milind J. Umekar; Md. Khalid Anwer; Hamad Ghaleb Dailah; Syam Mohan; Tapan Behl (Neurotoxicity Research, 2023)

RETRACTED ARTICLE: Nanosilver-functionalized polysaccharides as a platform for wound dressing - Syam Mohan; Pranay Wal; Kamla Pathak; Madhusmruti Khandai; Tapan Behl; Hassan A. Alhazmi; Gulrana Khuwaja; Asaad Khalid (Environmental Science and Pollution Research, 2023)

Insights into the pivotal role of statins and its nanoformulations in hyperlipidemia - Sukhbir Singh; Ishrat Zahoor; Neelam Sharma; Tapan Behl; Neha Kanojia; Aayush Sehgal; Syam Mohan; Yosif Almoshari; Ahmad Salawi; Lotfi Aleya; Simona Bungau (Environmental Science and Pollution Research, 2022)

Pathogenesis and management of traumatic brain injury (TBI): role of neuroinflammation and anti-inflammatory drugs - Sunishtha Kalra; Rohit Malik; Govind Singh; Saurabh Bhatia; Ahmed Al-Harrasi; Syam Mohan; Mohammed Albratty; Ali Albarrati; Murtaza M. Tambuwala (Inflammopharmacology, 2022)
Traumatic brain injury (TBI) is an important global health concern that represents a leading cause of death and disability. It occurs due to direct impact or hit on the head caused by factors such as motor vehicles, crushes, and assaults. During the past decade, an abundance of new evidence highlighted the importance of inflammation in the secondary damage response that contributes to neurodegenerative and neurological deficits after TBI. It results in disruption of the blood–brain barrier (BBB) and initiates the release of macrophages, neutrophils, and lymphocytes at the injury site. A growing number of researchers have discovered various signalling pathways associated with the initiation and progression of inflammation. Targeting different signalling pathways (NF-κB, JAK/STAT, MAPKs, PI3K/Akt/mTOR, GSK-3, Nrf2, RhoGTPase, TGF-β1, and NLRP3) helps in the development of novel anti-inflammatory drugs in the management of TBI. Several synthetic and herbal drugs with both anti-inflammatory and neuroprotective potential showed effective results. This review summarizes different signalling pathways, associated pathologies, inflammatory mediators, pharmacological potential, current status, and challenges with anti-inflammatory drugs.

Targeting therapeutic approaches and highlighting the potential role of nanotechnology in atopic dermatitis - Sukhbir Singh; Tapan Behl; Neelam Sharma; Ishrat Zahoor; Sridevi Chigurupati; Shivam Yadav; Mahesh Rachamalla; Aayush Sehgal; Tanveer Naved; Pritima; Sandeep Arora; Saurabh Bhatia; et al. (Environmental Science and Pollution Research, 2022)